Faktor-Faktor Yang Dipertimbangkan Investor Dalam Melakukan Investasi - Linda Ariany Mahastanti (Universitas Airlangga, 2011)
Investor has many options in an investment with the current number of investment instruments. Previous studies of retail investor behavior have examined motivation from economic perspectives or studied relationships between economic, behavioral and demographic variables. Examination of the various utility-maximization and behavioral variables underlying individual investor behavior provides a more comprehensive understanding of the investment decision process. This research will examine the seven factors that considered investors' decisions to invest, and investor behavior in taking the decision to invest. The data used are primary data that obtained by sending questionnaires through via email at Danareksa investors domiciled in Salatiga and Semarang. The analysis method used is tabulation frequencies and cross tabulation (Crosstab). Based on the results of the research, it is known that the factors that considered investor' decisions is Neutral Information and Accounting Information factor. For the result of demographic aspects effect research against investment decision is investor who are aged 25-29 and 50-54 years which is considered all of the factors. While for sex, female consider many factors than male. For educational level with high educational level makes the investor pay attention to the factors that associated with investment decisions, and investors who invest for 1-3 years old considering many factors before making investment decisions.